Hydrological Controls on Mineralisation in the Active Epithermal Environment, Taupo Volcanic Zone (TVZ), New Zealand - S F. Simmons (The Australasian Institute of Mining and Metallurgy, 2005)
At Broadlands-Ohaaki geothermal system, TVZ, mineral distribution patterns in geothermal wells are analogous to those in epithermal veins. Fluid flow through geothermal wells is focused over vertical intervals >500 m with discharge at rates up to 90 l/s. Focused flow at similar rates also occurs in natural systems where hydrothermal eruption vents provide enhanced vertical permeability. These vents are commonly aligned with the tectonic fabric, indicating fault control at depth. We suggest that host rock strength and structural context exert significant control on the hydrological regime conducive to epithermal mineralisation.